Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Gramedia Asri Media Cabang Emerald Bintaro - Syarah Amalia; Mahendra Fakhri (Jurnal Computech & Bisnis (e-Journal), 2016)
This study aims to determine the influence of motivation on employees’ performance at PT. Gramedia Asri Media Emerald Bintaro. The issues in this study was how motivation and employees performance at the Gramedia Asri Media Emerald Bintaro in achieving the performance of employees who have not met the targets and expectations set by PT. Gramedia Asri Media Emerald Bintaro. This study uses quantitative descriptive research and causal with population off all the employees at PT.Gramedia Emerald Bintaro, the number of respondents were 51 respondents. Then, for data analysis used descriptive analysis and simple linear regression analysis. Based on the results of hypothesis test, overall motivation to work is partially significant effect on employees performance at PT.Gramedia Asri Media Emerald Bintaro. Based on the coefficient of determination, motivation to work affect employees performance by 68,06% and 31,94% were affected by other variables, are not examined in this research. Keywords: motivation, motivation to work, performance.